Emergency medical service utilization and timely treatment among acute ischemic stroke patients in Beijing from 2018 to 2021. (30th April 2023) - Ding, Kexin; Chen, Hui; Wang, Yong; Liu, Hongmei; Zhang, Wenzhong; Wu, Yiqun
Abstract : Background and importance: Activation of emergency medical services (EMS) is recommended for timely reperfusion therapy for acute ischemic stroke (AIS). The association of EMS utilization and time intervals from hospital arrival to a series of necessary procedures before reperfusion therapy was rarely investigated. Objective: The objective of this study is to investigate the association of EMS utilization with the time intervals from hospital arrival to therapy in patients with AIS. Design: Observational study. Settings and participants: Medical records for AIS in all emergency departments in Beijing were obtained from January 2018 to December 2021. Intervention or exposure: Patients transported by ambulance were defined as the EMS group, whereas others as the non-EMS group. Outcome measures and analysis: Door-to-imaging time (DIT), door-to-needle time (DTN) and door-to-puncture time (DTP) were compared between the two groups. Main results: There were 11 190 (46%) and 13 106 (54%) AIS patients in the EMS and non-EMS groups. Compared with the non-EMS group, patients in the EMS group were more likely to receive intravenous thrombolysis or endovascular therapy (OR, 1.81; 95% CI, 1.68–1.94). For intravenous thrombolysis therapy, the DIT, ITN (time in minutes from obtaining the first brain imaging to tPA delivery) and DTN times in the EMS group were significantly shorter with time differences between the two groups of −1.1 (95% CI, −1.1 to −1.1) min, −2.6 (−2.6 to −2.6) min, and −3.7 (−3.8, −3.7) min, respectively. The proportion of DIT ≤25 min, DTN ≤45 min or DTN ≤60 min was significantly higher in the EMS group (OR, 1.03, 95% CI, 1.02–1.05; 1.11, 1.07–1.14; 1.05, 1.03–1.07). For endovascular therapy, the differences in DIT, ITP (time in minutes from obtaining the first brain imaging to groin puncture) and DTP times between the EMS and non-EMS groups were +1.1 (1.0–1.2) min, −3.8 (−4.2 to −3.5) min, −2.7 (−3.1 to −2.4) min, respectively, but no significant association was observed between EMS usage and the proportion of DIT ≤25 min or DTP ≤90 min. Conclusion: In this observational study, the use of EMS for patient with AIS was associated with a shorter time from hospital arrival to intravenous thrombolysis and endovascular therapy.